Autonomic nervous system function in childhood migraine - Yakinci, C; Mungen, B; Er, H; Durmaz, Y; Karabiber, H (Blackwell Science Asia, 1999)
Background: Although the pathogenesis of migraine is controversial, autonomic nervous system (ANS) dysfunction has been reported in patients with adult migraine in recent years. The present study was planned to investigate ANS function in childhood migraine. Methods: The migraine and control groups consisted of 25 migraineur and 30 healthy children, respectively. Orthostatic test, sustained handgrip, Valsalva ratio, 30/15 ratio and heart rate responses to deep breathing were used as non-invasive ANS function tests in both groups. Results: In the orthostatic test, systolic (SBP) and diastolic blood pressures (DBP) were higher in the upright than the supine position in the migraine group, but were higher in the supine than upright position in the control group. In the sustained handgrip test, the mean difference in SEP was higher in the migraine than the control group (P = 0.0278), but there was no significant difference in DBP between migraine and control groups (P = 0.107). The Valsalva ratio was higher in the migraine than the control group (P = 0.0002), as was the 30/15 ratio (P = 0.0108). Heart rate responses to deep breathing were not different between the migraine and control groups (P = 0.749). Conclusions: Our results demonstrate ANS dysfunction, with hyperactivity of both the sympathetic and parasympathetic nervous system, in children with migraine.
Keywords: autonomic nervous system; childhood; handgrip test; migraine; orthostatic test; Valsalva maneuver